Comparative analysis of cranial suture complexity in the genus Caiman (Crocodylia, alligatoridae) - MONTEIRO,L. R. (2000)
The variation in degrees of interdigitation (complexity) in cranial sutures among species of Caiman in different skull regions was studied by fractal analysis. Our findings show that there is a small species effect in the fractal dimension of cranial sutures, but most variation is accounted for by regional differentiation within the skull. There is also a significant interaction between species and cranial regions. The braincase sutures show higher fractal dimension than the facial skull sutures for all three species. The fractal dimension of nasal-maxilla suture is larger in Caiman latirostris than in the other species. The braincase sutures show higher fractal dimensions in C. sclerops than in the other species. The results suggest that different regions of the skull in caimans are under differential functional stress and the braincase sutures must counteract stronger disarticulation forces than the facial sutures. The larger fractal dimension shown by C. latirostris in facial sutures has probably a functional basis also. Caiman latirostris is known to have preferences for harder food items than the other species.